Investigating lake sediments and peat deposits with geophysical methods - A case study from a kettle hole at the Late Palaeolithic site of Tyrsted, Denmark. (30th August 2020) - Corradini, Erica; Eriksen, Berit Valentin; Mortensen, Morten Fischer; Nielsen, Martin Krog; Thorwart, Martin; Krüger, Sascha; Wilken, Dennis; Pickartz, Natalie; Panning, Diana; Rabbel, Wolfgang
Abstract: Kettle holes are common ice decay features in formerly glacial landscapes like those in Southern Scandinavia and Northern Germany. Here the kettle holes are represented either as dry depressions, wetland areas or lakes. However, the majority of these features are silted and part of the present farmland. We investigated a small kettle hole at Tyrsted, near the township of Tyrsted, south of Horsens (Denmark) with the aim to determine the extension and depth of this feature using geophysical methods. A former excavation at Tyrsted carried out from the Horsens Museum in 2017 at a neighboring site revealed Late Palaeolithic flint of the Bromme type and worked reindeer antlers. This connection in a Late Glacial horizon is unique not only in a Danish context and it can help to improve and clarify the dating of the Bromme culture. We used ground penetrating radar (GPR), electromagnetic induction (EMI) and electrical resistivity tomography (ERT) to estimate the extension of the kettle hole ( 16 m × 25 m). Shear wave reflection and refraction seismics (SH Seismics) were able to detect the bottom sediment of the former lake at about 5 m depth. Furthermore, a seismic event at about 1.30 m depth is visible which can be associated to the transition between the Allerød and Younger Dryas sediment making the detection of the Bromme horizon possible. After the non-invasive investigation, a location for an open excavation has been chosen in a way to groundtruth the geophysical results allowing the direct comparison with the stratigraphy. These results allow the archaeologists to identify key excavation areas focused on the investigation of the Allerød and Younger Dryas layers in a way to improve the dating information about the Bromme horizon collected so far. Furthermore, geophysical investigations together with excavations will enable the archaeological and palaeoenvironmental research groups to search large scale palaeolandscapes for these very rare, but highly important finds. Highlights: SH-wave seismics enables exploring the kettle hole down to its full depth. The detection of the Bromme horizon is possible with geophysical methods. Ground truthing the results with corings allows the reconstruction of the stratigraphy to plan test excavation.